A diagnosis of the current state of the teaching of english offered to the Departaments and Schools of the Faculty of Arts and Humanities by the Foreing Languages Department of the University of El Salvador - Canjura Palma, Manuel de Jesús; Márquez Segovia, Ana Ruth; Ruiz Saravia, Jensy Soyett (2024)
For more than two decades, the Foreign Languages Department of the Faculty of Arts and Humanities has taught English courses to different Schools of the University of El Salvador whenever it has been required by them. According to the faculty, many different schools include the English subject either as part of the curricula or as an elective course, but because many of these Departments and Schools do not count on specialized personnel to teach those courses, the Foreign Languages Department through the “Service Area,” teaches English to those schools and Departments that require this service. The present project makes reference to the current state of the English TeachingLearning Process to students from different schools of the Faculty of Arts and Humanities. This research was focused on two aspects mainly. First, it focused on the kind of service provided to those schools by the Foreign Languages Department; and second to find out if the main objectives of each major benefited with this service are accomplished.